Pengaruh Penerapan Sistem Informasi Inventaris Udayana Dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pada Satuan Kerja Universitas Udayana - I Wayan Angga Mei Sedana Yoga; Kadek Dewi Padnyawati (UNHI Press, 2022)
This study was conducted to determine the effect of the application of the Udayana inventory information system and intern control system on the quality of financial reports at the Udayana University work unit. The samples in this study were employees at the Sub-Division of Accounting and Reporting of State Property (BMN Aklap), employees at the Sub-Division of Accounting and Financial Reporting (Aklap Finance) and Udayana inventory information system operators at Udayana University so that a sample of 56 people was obtained from the total employees at the Udayana University work unit. The data collection technique used a questionnaire which was analyzed by multiple linear regression analysis using SPSS software in data processing. This study shows that the implementation of the Udayana inventory system has a positive and significant effect on the Quality of Financial Reports and the Internal Control System has a positive and significant effect on the Quality of Financial Reports.